# Solve for a -8a=8(a+3)

-8a=8(a+3)
Simplify 8(a+3).
Apply the distributive property.
-8a=8a+8⋅3
Multiply 8 by 3.
-8a=8a+24
-8a=8a+24
Move all terms containing a to the left side of the equation.
Subtract 8a from both sides of the equation.
-8a-8a=24
Subtract 8a from -8a.
-16a=24
-16a=24
Divide each term by -16 and simplify.
Divide each term in -16a=24 by -16.
-16a-16=24-16
Cancel the common factor of -16.
Cancel the common factor.
-16a-16=24-16
Divide a by 1.
a=24-16
a=24-16
Simplify 24-16.
Cancel the common factor of 24 and -16.
Factor 8 out of 24.
a=8(3)-16
Cancel the common factors.
Factor 8 out of -16.
a=8⋅38⋅-2
Cancel the common factor.
a=8⋅38⋅-2
Rewrite the expression.
a=3-2
a=3-2
a=3-2
Move the negative in front of the fraction.
a=-32
a=-32
a=-32
The result can be shown in multiple forms.
Exact Form:
a=-32
Decimal Form:
a=-1.5
Mixed Number Form:
a=-112
Solve for a -8a=8(a+3)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top